2006
DOI: 10.1080/01926230600611836
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Effects of Anti-Angiogenic Compounds on the Epiphyseal Growth Plate

Abstract: The formation of new blood vessels from a pre-existing vascular bed, termed "angiogenesis," is of critical importance for the growth and development of the animal since it is required for the growth of the skeleton during endochondral ossification, development and cycling of the corpus luteum and uterus, and for the repair of tissues during wound healing. "Vasculogenesis," the de novo formation of blood vessels is also important for the proper function and development of the vascular system in the embryo. New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 215 publications
3
67
0
Order By: Relevance
“…This results in accumulation of vertical columns (chondrons) of hypertrophic chondrocytes within an otherwise normal but thickened growth plate. In this study, we observed growth plate dysplasia (and in 1 animal articular cartilage dysplasia) in the rabbit that appeared morphologically identical to the same changes observed in rodents treated with a range of antiangiogenic compounds (Hall, Westwood, and Wadsworth 2006), and where the mechanism has been well elucidated (Gerber, Vu et al 1999). Since the active metabolite of fostamatinib, R406, inhibits VEGFR and FGFR family members with a similar potency to the intended therapeutic target, SYK (IC 50 4-60 nM; Braselmann et al 2006;Rolf et al 2015), and since the primary target, SYK, plays no known role in osteogenesis, the dysplastic changes noted in this study are believed to be due to angiogenic inhibition of VEGF and/or family FGF receptors leading to the retention of hypertrophic chondrocytes secondary to delayed vascular invasion.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This results in accumulation of vertical columns (chondrons) of hypertrophic chondrocytes within an otherwise normal but thickened growth plate. In this study, we observed growth plate dysplasia (and in 1 animal articular cartilage dysplasia) in the rabbit that appeared morphologically identical to the same changes observed in rodents treated with a range of antiangiogenic compounds (Hall, Westwood, and Wadsworth 2006), and where the mechanism has been well elucidated (Gerber, Vu et al 1999). Since the active metabolite of fostamatinib, R406, inhibits VEGFR and FGFR family members with a similar potency to the intended therapeutic target, SYK (IC 50 4-60 nM; Braselmann et al 2006;Rolf et al 2015), and since the primary target, SYK, plays no known role in osteogenesis, the dysplastic changes noted in this study are believed to be due to angiogenic inhibition of VEGF and/or family FGF receptors leading to the retention of hypertrophic chondrocytes secondary to delayed vascular invasion.…”
Section: Discussionmentioning
confidence: 63%
“…Inhibition with bevacizumab, sunitinib, and recentin (which inhibit the VEGF pathway) as well as PD176067 (which inhibits the FGF pathway), all induce epiphyseal growth plate dysplasia in rats and monkeys Patyna et al 2008;Wedge et al 2005;Brown et al 2005). Inhibition of angiogenesis by other classes of molecule, such as MMPs (Vu et al 1998), and vascular targeting agents (Hall, Westwood, and Wadsworth 2006) also induces growth plate dysplasia, suggesting that this change is pathognomonic for antiangiogenic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Common toxicities thought to be related to on-target effects include fatigue, hypertension (Izzedine et al 2007(Izzedine et al , 2009Pande et al 2007), proteinuria, delayed wound healing, and chemical hypothyroidism (often without clinical symptoms) (Veronese et al 2006;Boehm et al 2010;Geiger-Gritsch et al 2010;Robinson et al 2010b). Several rare side effects have also been reported in multiple trials and include bleeding and/or thrombosis (which can be severe or fatal), intestinal and nasal septal perforation (Hapani et al 2009), effects on growth plates (Hall et al 2006), and posterior reversible encephalopathy syndrome (PRES), also known as reversible posterior leukoencephalopathy syndrome (RPLS) (Artunay et al 2010). Initial concerns about frequent severe and fatal hemorrhages have not been observed clinically for most tumor types, although this potential side effect continues to be of concern, particularly in certain tumor subtypes (Hapani …”
Section: Toxicities Of Vegf Pathway Inhibitorsmentioning
confidence: 99%
“…Histological assessment was focused primarily on tissues that were known to be responsive to angiogenic inhibition in the rodent, namely, the ovary, adrenal glands, epiphyseal growth plate, and incisor teeth. In these tissues, treatment with VEGFR inhibitors had previously been shown to induce reliable signature changes of antiangiogenesis characterized by growth plate dysplasia (Gerber et al 1999;Wedge et al 2005;Hall, Westwood, and Wadsworth 2006), ovarian (and uterine) atrophy (Ferrara et al 1998;Wulff et al 2002;Wedge et al 2005), incisor tooth dental dysplasia (Patyna et al 2008;Fletcher et al 2010;Hall, Westwood, and Wadsworth 2006), and adrenal gland cortical necrosis and hemorrhage (Patyna et al 2008).…”
Section: Ovarymentioning
confidence: 99%
“…In the growing rodent, for example, treatment with vascular endothelial growth factor receptor (VEGFR) inhibitors results in a constellation of target organ toxicity in angiogenic-dependent tissues such as the growth plate, ovary, incisor tooth, and adrenal gland characterized by growth plate dysplasia (Gerber et al 1999;Wedge et al 2005;Hall, Westwood, and Wadsworth 2006), ovarian (and uterine) atrophy (Ferrara et al 1998;Wulff et al 2002;Wedge et al 2005), incisor tooth dental dysplasia (Patyna et al 2008;Fletcher et al 2010;Hall, Westwood, and Wadsworth 2006), and adrenal gland cortical necrosis and hemorrhage (Patyna et al 2008). Taken together, this pattern of target organ toxicity may be regarded as a preclinical signature of antiangiogenic effect (Hall 2005).…”
Section: Introductionmentioning
confidence: 99%